2021
DOI: 10.1055/s-0041-1735964
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Microarchitecture Deficit in Patients with Hemophilia Is Influenced by Arthropathy, Hepatitis C Infection, and Physical Activity

Abstract: Low bone mineral density (BMD) is common in patients with hemophilia (PWHs). The aim of the present study was to describe BMD and microarchitecture in PWHs in Northern Germany and to determine factors contributing to possible skeletal alterations. Demographic characteristics, BMD and microarchitecture, bone metabolism markers, and orthopaedic joint score (OJS) were assessed during routine check-ups. Areal BMD was assessed by dual-energy X-ray absorptiometry (DXA) at the hip and lumbar spine. Volumetric BMD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Trabecular alterations at the tibia were associated with orthopedic joint damage scores and hepatitis C virus status. 25 Taken together, these findings suggest that microarchitectural deficits start at an early age in haemophilia, and poor bone accrual and strength can be expected to worsen over time.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Trabecular alterations at the tibia were associated with orthopedic joint damage scores and hepatitis C virus status. 25 Taken together, these findings suggest that microarchitectural deficits start at an early age in haemophilia, and poor bone accrual and strength can be expected to worsen over time.…”
Section: Discussionmentioning
confidence: 72%
“…Cortical deficits at the radius were influenced by lower BMI, low‐grade inflammation, and treatment regimen: there was higher cortical thickness in patients on primary prophylaxis. Trabecular alterations at the tibia were associated with orthopedic joint damage scores and hepatitis C virus status 25 . Taken together, these findings suggest that microarchitectural deficits start at an early age in haemophilia, and poor bone accrual and strength can be expected to worsen over time.…”
Section: Discussionmentioning
confidence: 76%
“…Besides, a majority of patients in this Indian study exhibited chronic arthritis, which hampers regular exercise. Physical activity is known to promote BMD enhancement [ 37 ]. Calcium intake among Indians falls significantly below daily requisites due to dietary habits [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of exercise affects bone mass and results in BMD not reaching its peak. Multiple studies [ 37 , 50 ] have suggested that sportive activity had a positive impact on BMD in PWH.…”
Section: Discussionmentioning
confidence: 99%